The quality of sleep of nursing professionals and the Covid-19 pandemic - Picoli , Mauricio; Santos , Giane Alves; Machado , Elisiane de Oliveira; Vizini , Simone Thais; Rosa , Fabio Silva da; Santos , Suimara; Chassot , Maicon Daniel; Campos , Rejane Silveira de; Bonatto , Vanessa Frighetto (Seven Editora, 2023)
Objective: to compare the quality of sleep of nursing professionals who worked in an adult intensive care unit with nursing professionals who worked in inpatient units during the Covid-19 pandemic. Method: This is a cross-sectional study. The selection of participants occurred intentionally using the snow ball methodology. The study included 27 participants, nurses and nursing technicians who worked in adult intensive care or adult hospitalization units caring for patients affected by Covid-19 and excluded professionals who regularly use sleep-inducing medications prior to the Covid-19 pandemic. Covid-19; or Individuals with sleep apnea. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (IQSP) instrument. The independent variables were classified as sociodemographic, work situations, lifestyle habits, nutritional status and presence of comorbidities. The analysis was carried out using descriptive and inferential statistics using SPSS v25.0 software. Data normality was tested using the Shapiro-Wilk test. Results: The sample of the present study was composed of men (22.4%) and women (77.8%) with an average age of 34.2 (±6.2) years. No significant correlations were found between the Sleep Quality Index and the analyzed variables. However, when analyzing whether there was any correlation between the questionnaire score and some continuous variables, such as the participants' weight, a moderate correlation was observed between the questionnaire score and the participants' weight r =0.469 p = 0.025. Conclusion: Despite not demonstrating statistical significance for the variables studied, the study considers the relationship between sleep quality and obesity, demonstrating statistical significance and corroborating the scientific literature. DOI:https://doi.org/10.56238/sevened2023.004-002